RENOVASI RUANG BACA SEBAGAI UPAYA PENINGKATAN MINAT BACA BAGI ANAK-ANAK PANTI ASUHAN KANA’AN JAYA - Mujiati Mujiati; Apolo Safanpo; Helen Gianditha Wayangkau; Alfian Chandra; Bernathius Julison (JURNAL PENGABDIAN PAPUA, 2023)
Kana'an Jaya Orphanage is one of the privately owned social institutions that was originally a shelter for abandoned children and orphans who came from several areas of political conflict in the Papuan Mountains. In 2019 there was a flash flood disaster that ravaged their building facilities. Some facilities, such as the reading room, were destroyed. Inadequate facilities for learning are certainly a factor in not realizing the development of human resources as desired by the Chair of the Foundation. So in accordance with the goals of the chairman of the foundation, the Community Service team renovated the reading room while also equipping reading facilities such as bookshelves, reading tables, reading books as well as repairing and maintaining parts of the room that can provide comfort and increase children's reading intentions. The method of implementing this community service program includes surveys on the availability of supporting facilities for children's libraries. Arrangement of a comfortable library space for children by providing library shelves and books. As a result, the procurement of a library at the orphanage can be carried out, with facilities provided in the form of 4 bookshelves and reading books. Furthermore, the handover of goods has been carried out to the chairman of the foundation and the head of the orphanage.Keywords: Reading Interest; Renovatio; Library